Quality management in dental health care: Present and future development - Tekić Jasmina; Majstorović Vidosav D.; Marković Dejan; Nikodijević Angelina; Stamenković Dragoslav (Serbian Medical Society - Dental Section, Belgrade, 2011)
The standards ISO 9000 series, brought in 1987, were the driving force for the development and application of quality management (QM) in various areas, including health care. Currently, there are over one million certificates for quality management (QMC), and they were main initiators of quality improvement. In addition to the model for quality management of products/services, other models are also in use. The aim of this study was to present methods and techniques for quality improvement of health services, with special emphasis on dental health care services (DHS), and possibility for enhancement.